From Lock-In to Phase-Out : Pathways Towards Fossil Fuel Subsidy Reform - Drake, Evan ; 0009-0005-0602-0138 (Lund University (Media-Tryck), 2025)
This dissertation investigates the political determinants of fossil fuel subsidy reform in OECD countries between 2009 and 2023. Despite widespread recognition of their economic inefficiency and environmental harm, fossil fuel subsidies remain entrenched, with OECD countries collectively sustaining around USD 100 billion in annual support. The research addresses why some governments successfully reduce these subsidies whilst others do not. It conceptualises these subsidies as critical mechanisms of "carbon lock-in" that entrench fossil fuel dependence and impede climate action. Drawing on multiple strands of political science literature, the dissertation develops an integrated analytical framework that considers the roles of institutional configurations, governing party preferences, policy processes, and affective polarisation in shaping reform trajectories. Using a mixed-methods approach and four complementary articles covering 34 OECD countries, the research identifies both structural and strategic pathways to reform. Key findings show that proportional representation and corporatist institutions are associated with lower subsidy levels, by offering electoral insulation and facilitating compensatory strategies. Governments led by environmentally committed parties tend to reduce subsidies, whereas market-liberal parties increase them—particularly when they hold parliamentary majorities. The study also introduces the concept of "dismantling by layering", where incremental policies such as carbon taxes erode subsidies indirectly, minimising direct political confrontation. Finally, the dissertation develops a research agenda and theoretical framework proposing how affective polarisation may constrain reform by transforming climate policies into partisan identity markers. Together, the findings suggest that the climate governance challenge is not primarily about identifying technically optimal policy instruments but about understanding the political conditions under which necessary policies become feasible—an analytical shift with profound implications for both academic research and policy practice in addressing the climate crisis.
Keywords: fossil fuel subsidies; climate policy; policy change; political polarisation; party systems; political economy; carbon taxes; OECD